Efektivitas Penggunaan Metode Demontrasi Terhadap PemahamanSiswa Pada Materi Interaksi Manusia Dengan Lingkungan MataPelajaran IPS TerpaduKelas VII MTs Negeri Surakarta 1 - Purnomo, Pamungkas Bayu aJI, Dra. Siti Taurat Aly, M.Pd (2016)
This research was conducted in MTs Negeri Surakarta 1. Purpose of this study to determine the effectiveness of method of demonstration for students' understanding on the matter of human interaction with the environment subjects integrated IPS class VII Mts Negeri Surakarta 1. Experimental design used in this study is a pretest-posttest control group design. The sample in the study uses 33 respondents. Data analysis using Paired Sample t Test. The results showed there is a difference between pre-test and postclass control is evidenced by the Sig <0.05 so that means that Ho is rejected and Ha accepted. There are differentiation also between pre-test and post experimental class as evidenced by the Sig <0,05 so Ho rejected and Ha accepted. There are differentiation between controlled and experiment class difference that can be seen the value of Sig <0,05 so Ho rejected and Ha is accepted that there are differences in the results of conventional methods with methods of demonstration. It can be concluded that the demonstration of effective learning methods.